A case of lymphomatoid granulomatosis masquerading as a lung abscess. Issue 9 (27th August 2004) - McCloskey, M; Catherwood, M; McManus, D; Todd, G; Cuthbert, R; Riley, M
Abstract : Lymphomatoid granulomatosis (LG) is a rare T cell rich, B cell non-Hodgkin's lymphoma which is difficult to diagnose. We present a patient with LG who demonstrated many of the difficulties in diagnosis and highlighted the importance of reviewing the diagnosis if treatment does not have the anticipated effect.